The Correlation Students Positive Perception And Motivation And Learn English - Masyeli Diana Pakpahan, Ahmad Laut Hasibuan (Pusdikra Publishing, 2022)
This study aims to determine: (1) the correlation between students' positive perceptions of English learning outcomes, (2) the correlation between students' learning motivation in learning English and student learning outcomes, and (3) the correlation between students' positive perceptions and students' learning motivation. in learning English on student learning outcomes at SMP N 1 DOLOK This type of research is a correlational study. The research subjects were 91 students of class VIII SMP N 1 DOLOK. Data collection techniques using questionnaires/questionnaires, and performance tests. The validity test uses the product moment correlation formula and the reliability test uses the Cronbach alpha formula. The data analysis technique uses the product moment correlation formula. The results showed that: (1) there was a significant correlation between students' interest in learning English and student learning outcomes. This is indicated by the calculated r value which is greater than r table (0.491> 0.207) and the significance value is 0.000 <0.05; (2) there is a significant correlation between students' learning motivation in learning English art and student learning outcomes. This is indicated by the value of r arithmetic greater than r table (0.546> 0.207) and a significance value of 0.000 <0.05; and (3) there is a significant correlation between students' positive perceptions and students' motivation to learn English together in learning English on student learning outcomes at SMP N 1 DOLOK. This is indicated by the correlation coefficient or R of 0.611> 0.207, and a significance value of 0.000 <0.05.